GROSS ANATOMY AND SURGICAL APPROACH TO THE HUMERAL SHAFT IN GIANT ANTEATER (MYRMECOPHAGA TRIDACTYLA) - Sesoko, Natalia Ferreira [UNESP]; Rahal, Sheila Canevese [UNESP]; Bortolini, Zara [UNESP]; Merlini, Natalie Bertelis [UNESP]; Teixeira, Carlos Roberto [UNESP] (Amer Assoc Zoo Veterinarians, 2016)
Anteater forelimbs are distinguished morphologically from domestic animals, especially due to their unique movement and their natural habits. A knowledge of the pectoral limb anatomy and the proper surgical approach are fundamental to success in osteosynthesis and other surgeries. This study aimed to describe the muscles and neurovascular structures of the pectoral limb and the surgical approach to the humeral shaft of the giant anteater (Myrmecophaga tridactyla). Dissections of the forelimbs of seven cadavers were performed to identify the major muscles and neurovascular structures. Three of these animals' contralateral forearms were used to simulate the surgical approach to the humeral shaft. Some specific characteristics of the muscle morphology were biceps muscle had two heads, triceps muscle had three heads, and there was an olecranon-epicondylar muscle. To expose the shaft of the humerus, it was necessary to incise the superficial pectoral muscle and separate the heads of the biceps muscle. Due to the anatomical characteristics of the humerus, the craniomedial approach was the most appropriate because it accommodated the anatomical peculiarities of the giant anteater.
Keywords: Anatomy; forelimb; giant anteater; morphology; Myrmecophaga tridactyla; surgery